2022
DOI: 10.18632/aging.204030
|View full text |Cite
|
Sign up to set email alerts
|

Effective biomarkers and therapeutic targets of nerve-immunity interaction in the treatment of depression: an integrated investigation of the miRNA-mRNA regulatory networks

Abstract: Background: Major depressive disorder (MDD) is an emotional condition that interferes with sufferers’ work and daily life. Numerous studies have found that miRNAs play a significant role in the development of MDD and can be utilized as a biomarker for its diagnosis and therapy. However, there have been few studies on nerve-immunity interaction treatment for the brains of MMD patients. Methods: The work is performed on microarray data. We analyzed the differences of miRNAs (GSE58105, GSE81152, GSE152267, and GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Especially their ability to overcome the blood-brain barrier, broaden new horizons for the studies on the interaction between central nervous system and peripheral tissues, for example, bone. Currently, it has been reported that the expression profile of miRNAs was significantly altered in patients with neuropsychiatric disorders(Rao et al, 2013; Wang, 2021; Wu et al, 2022; Żurawek & Turecki, 2021). And some of these miRNAs contained in EVs play a vital role in central regulation in bone metaboliasm.…”
Section: Discussionmentioning
confidence: 99%
“…Especially their ability to overcome the blood-brain barrier, broaden new horizons for the studies on the interaction between central nervous system and peripheral tissues, for example, bone. Currently, it has been reported that the expression profile of miRNAs was significantly altered in patients with neuropsychiatric disorders(Rao et al, 2013; Wang, 2021; Wu et al, 2022; Żurawek & Turecki, 2021). And some of these miRNAs contained in EVs play a vital role in central regulation in bone metaboliasm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a research team ever accumulated evidence of the "immune metabolism" subtype of MDD by clustering specific behavioral symptoms that reflected the balance between energy intake and consumption. [15] Herein, 10 hub genes of AS and MDD were identified and obtained by GSEA enrichment analysis involving nuclear transcribed m RNA catabolic process, protein targeting, ribosomal subunit, translational initiation, and viral gene expression. It could be noted from the analysis of the proportion of immune cells in AS and MDD datasets that Neutrophils, T cells CD8, T cells CD4 naive, T cells CD4 memory resting, T cells CD4 memory activated and Tregs accounted for a high proportion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a research team ever accumulated evidence of the “immune metabolism” subtype of MDD by clustering specific behavioral symptoms that reflected the balance between energy intake and consumption. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Also, hsa04613 has been separately connected [84] to depression and to fatigue (in patients receiving chemotherapy for cancer) [85]; fatigue is also a characteristic symptom of depression. hsa05203 has been separately connected to Post Traumatic stress Disorder, a major predictor for depression [86], epigenetic contributions to human behavior [87], risk for first episode psychosis [88] and schizophrenia [89] and hsa05322 has been separately associated with oxidative stress and cognitive function in schizophrenia [90] and antipsychotics-induced parkinsonism [91].…”
Section: Discussionmentioning
confidence: 99%